Application of superconducting magnetic energy storage in electrical power and energy systems: a review. (16th May 2017) - Vulusala G, Venkata Suresh; Madichetty, Sreedhar
Summary: Superconducting magnetic energy storage (SMES) is known to be an excellent high‐efficient energy storage device. This article is focussed on various potential applications of the SMES technology in electrical power and energy systems. SMES device founds various applications, such as in microgrids, plug‐in hybrid electrical vehicles, renewable energy sources that include wind energy and photovoltaic systems, low‐voltage direct current power system, medium‐voltage direct current and alternating current power systems, fuel cell technologies and battery energy storage systems. An extensive bibliography is presented on these applications of SMES. Also, some conclusive remarks in terms of future perspective are presented. Also, the present ongoing developments and constructions are also discussed. This study provides a basic guideline to investigate further technological development and new applications of SMES, and thus benefits the readers, researchers, engineers and academicians who deal with the research works in the area of SMES. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Application of superconducting magnetic energy storage devices was received. Several energy control schemes were discussed. Application of future transportation, that is, electric vehicle was discussed in detail. Future prospective of superconducting magnetic energy storage was elaborated in detail.